Architecting Self-Governing AI Systems: Field Applications of Decentralized Intelligence in Autonomous Digital Operations - Sawant, Shreyas Subhash (International Journal of Computing and Engineering, 2025)
The proliferation of autonomous systems across critical infrastructure, supply chains, and digital services has revealed fundamental constraints in centralized AI architectures, where traditional command-and-control frameworks struggle with dynamic complexity and scale demands of modern digital ecosystems. Self-Governing AI Systems (SGAS) emerge as a paradigmatic shift toward distributed intelligence, enabling autonomous agents to collectively manage digital operations through emergent coordination rather than centralized orchestration. This architectural innovation draws inspiration from biological systems, distributed computing principles, and game-theoretic frameworks to create resilient, adaptive, and scalable AI infrastructures. The SGAS framework encompasses three foundational pillars: autonomous decision nodes that combine local sensory capabilities with contextual reasoning, distributed consensus mechanisms that ensure system coherence without centralized control, and adaptive coordination protocols that facilitate dynamic collaboration through negotiation-based resource allocation. Implementation methodologies address communication architectures, decision-making algorithms, and integration strategies through layered approaches that separate concerns while maintaining system coherence. Field validation across real-time infrastructure orchestration, autonomous compliance enforcement, and multi-agent logistics routing demonstrates superior performance characteristics compared to centralized alternatives. The distributed architecture eliminates communication bottlenecks, enables immediate decision-making based on local information, and provides enhanced fault tolerance where individual node failures do not compromise overall system functionality. Performance evaluation reveals consistent improvements in decision-making speed, robustness to system failures, near-linear scalability, and substantial resource utilization efficiency gains.